Bactericera tremblayi (Wagner, 1961) (Hemiptera: Triozidae): The Prevalent Psyllid Species in Leek Fields of Northwestern Spain - Yolanda Santiago-Calvo; Laura Baños-Picón; Diego Flores-Pérez; M. Carmen Asensio-S.-Manzanera (Insects, 2023)
Bactericera tremblayi (Wagner, 1961) (Hemiptera: Triozidae), the onion and leek psyllid, belongs to the Bactericera nigricornis Förster complex, along with B. trigonica and B. nigricornis. In contrast to the other two species, there has been a notable absence of studies examining the distribution and seasonal occurrence of B. tremblayi, despite its association with significant issues in leek crops. Surveys were conducted between 2017 and 2020 in the main leek-growing area of Castile and Leon (Spain). An extensive survey encompassing 29 distinct plots was monitored with sweep nets and visual inspection, counting plants with immature forms at three times in the crop cycle. Additionally, a total of seven seasonal monitoring surveys were conducted in the same area of study. Plots were monitored every ten days, employing three distinct sampling methods including horizontal green tile water traps, sweep nets, and visual inspection, counting the juvenile stages by plant. The results revealed that B. tremblayi predominated as the primary species of jumping plant-lice in leek crops throughout the entire crop cycle. To date, there exists no documented incidence of pathogenic agents within symptomatic leeks. Consequently, the manifestation of severe symptoms is highly likely to be a direct consequence of the feeding activity of the onion psyllid. Populations of B. tremblayi were present in leek crops from May–July to harvest (September–November). Adults were captured in horizontal green water traps several days before they were found in sweep net samples, making the former effective in capturing early immigrant individuals. The maximum peaks of B. tremblayi were observed at the end of the crop cycle, particularly during late-season cycles characterized by lower mean temperatures. During observations made in a controlled environment, temperature exerted a significant influence on the developmental time of all stages of B. tremblayi. The complete development from egg to adult occurred within a temperature range of 15 to 25 °C. At 30 °C, the survival of eggs and N1 nymphs was limited and B. tremblayi did not complete its developmental cycle. The optimum temperature for the development of B. tremblayi provided by the models used was close to 24 °C with the application of Briere, Taylor, and Lactin models and around 21 °C with the SSI model. These results provided a good adjustment in predicting the survival patterns of B. tremblayi under the studied environmental conditions.